Deep learning techniques and optimization strategies in big data analytics - Thomas, J. Joshua, 1973- (Advances in systems analysis, software engineering, and high performance computing (ASASEHPC) book series., 2020)
"This book examines the application of artificial intelligence in machine learning, data mining in unstructured data sets or databases, web mining, and information retrieval"--